1996
DOI: 10.1016/0014-5793(96)00272-4
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of glutathione S‐conjugates by a carboxypeptidase in the plant vacuole

Abstract: For plants, glutathione conjugation is a major pathway to detoxify organic xenobiotic. Glutathione S-conjugates (SG-conjugates) are formed in the cytosol, the in vitro transport over the tonoplast has been described and a final storage in the vacuole has been postulated. We show here that alachlor rapidly accumulates as GS-conjugates in the plant vacuole and that the first step of its degradation, the formation of the respective Tglutamylcysteinyl-S-conjugate, is catalyzed by a vacuolar carboxypeptidase. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
85
1
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(91 citation statements)
references
References 12 publications
2
85
1
3
Order By: Relevance
“…In situ cytosolic glutathionation of monochlorobimane to its fluorescent derivative, bimane-GS, and accumulation of the latter in the vacuoles of protoplasts and cell suspension cultures has been demonstrated (37) as has a greater than 50-fold accumulation of alachor-GS in the vacuoles of intact barley leaves (38). Likewise, it is evident that an MRP-like functionality is responsible for the vacuolar uptake of both glutathionated and nonglutathionated dyes by barley aleurone cells (39).…”
Section: Discussionmentioning
confidence: 99%
“…In situ cytosolic glutathionation of monochlorobimane to its fluorescent derivative, bimane-GS, and accumulation of the latter in the vacuoles of protoplasts and cell suspension cultures has been demonstrated (37) as has a greater than 50-fold accumulation of alachor-GS in the vacuoles of intact barley leaves (38). Likewise, it is evident that an MRP-like functionality is responsible for the vacuolar uptake of both glutathionated and nonglutathionated dyes by barley aleurone cells (39).…”
Section: Discussionmentioning
confidence: 99%
“…SCPL enzymes also play a role in herbicide metabolism, in which a SCPL has been shown to catalyze the first step in the catabolism of an alachlor glutathione S-conjugate by removing the terminal glycine residue of the glutathione moiety (Wolf et al, 1996). On the basis of these and other studies, investigators have suggested various functions for SCPL enzymes, ranging from protein turnover and C-terminal processing to roles in wound responses and xenobiotic metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, safener-inducible genes for serine carboxypeptidase and a lactoylglutathione lyase (carbon-sulfur lyase) family protein may be involved in phase IV of the detoxification process (Table 2). Serine carboxypeptidase contributes to the degradation of GSH conjugates to their respective Cys derivatives (Wolf, Dietz & Schroder 1996), which may be further metabolized by carbon-sulfur lyases (Brazier-Hicks et al 2008). It thus seems that the entire xenobiotic detoxification machinery is induced at the transcript level after safener treatment in aerial tissues of Arabidopsis, confirming previous conclusions that it is not safener inducibility per se that distinguishes monocots and dicots with respect to safener efficacy.…”
Section: Safeners Induce the Expression Of The Endogenous Detoxificatmentioning
confidence: 99%